1997
DOI: 10.1175/1520-0442(1997)010<1154:gsaovp>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Global-Scale Assessment of Vegetation Phenology Using NOAA/AVHRR Satellite Measurements

Abstract: Phenology and associated canopy development exert a strong control over seasonal energy and mass exchanges between the earth's surface and the atmosphere. Satellite measurements are used to assess main phenological stages of the vegetation at the global scale. The authors propose a method to derive the start, the maximum, the end, and the length of the vegetation cycle, based on the analysis of temporal series of weekly vegetation index, at a resolution of 1Њ lat ϫ 1Њ long for year 1986. Global maps of these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
205
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(217 citation statements)
references
References 58 publications
3
205
0
2
Order By: Relevance
“…Over savannah, a decrease of LAI centered on August is striking for MODIS and, to a lesser extent for CYCLOPES. This could be attributed to the well known little dry season affecting these areas during August and September but it has been associated to the increase of the cloud cover at this period of the year by Moulin et al [1997]. The absence of a significant decrease of rainfall during this period tends to corroborate this assumption (Figure 6).…”
Section: Ctessel Against the Satellite-derived Lai And Bias Correctionmentioning
confidence: 57%
See 1 more Smart Citation
“…Over savannah, a decrease of LAI centered on August is striking for MODIS and, to a lesser extent for CYCLOPES. This could be attributed to the well known little dry season affecting these areas during August and September but it has been associated to the increase of the cloud cover at this period of the year by Moulin et al [1997]. The absence of a significant decrease of rainfall during this period tends to corroborate this assumption (Figure 6).…”
Section: Ctessel Against the Satellite-derived Lai And Bias Correctionmentioning
confidence: 57%
“…Another striking feature is also the artificial break in the growing phase of the LAI for the MODIS product during the spring months. It is certainly an artifact of the satellite products due to bad atmospheric corrections [Moulin et al, 1997] as previously discussed. Nevertheless, it has been minimized thanks to the smoothing filter with the upper envelope.…”
Section: Lai Time Seriesmentioning
confidence: 91%
“…The beginning of a new phenological cycle can then occur. This means that several phenological cycles can theoretically occur in 1 year (for example, spring and autumn greening of grasses in Mediterranean-type climates [Moulin et al, 1997]). …”
Section: Photosynthesis and Stomatal Conductancementioning
confidence: 99%
“…Therefore, NDVI cannot clearly discriminate the growing period from other conditions with a simple site-independent single threshold. We must consider the presence or absence of snow/water cover and understory vegetation for each target when we use NDVI, as pointed out by several studies [24][25][26][27]. Furthermore, as Nagai et al [13] have reported, the canopy condition of autumn coloring corresponded to different NDVI values from year to year.…”
Section: Applicability Of Grvi As An Indicator Of Vegetation Phenologymentioning
confidence: 99%